Efektifitas Kebijakan Pemerintah Dalam Menghapus Kekerasan Terhadap Perempuan - Nabila Zatalin; M. Alief Fadllika Yudhistira (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Violence against women is a human rights violation that remains prevalent in Indonesia, despite various government policies. This study examines the effectiveness of government policies in eliminating violence against women, particularly in the context of legal protection and policy implementation in the field. The research question examines the extent to which these policies are able to prevent and address violence against women systematically and sustainably. This study uses a normative juridical method with a legislative approach and case studies of the implementation of Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence. The results indicate that despite progress in regulation, policy effectiveness is still hampered by minimal coordination between institutions, a lack of understanding among law enforcement officials, and limited access to support services for victims. Therefore, strengthening policy implementation through training, outreach, and integrated supervision is needed to optimally protect women.